Reformulating the Governance of Carbon Economic Value Based on Pancasila Ethics and Climate Justice to Address Inequality and Prevent Crimes in Indonesia’s Carbon Trading - Silverius Y. Soeharso; Agus Surono; Adnan Hamid; Phattharawadee Rangsimanop (Journal Evidence Of Law, 2025)
This article critically examines the urgency of reformulating the governance framework of Carbon Economic Value (CEV) in Indonesia by integrating the ethical principles of Pancasila as Indonesia’s national ideology and climate justice. The increasing risks of inequality, greenwashing, and transnational environmental crimes in voluntary and compliance carbon markets demand a just, adaptive, and integrity-based legal approach. By highlighting the current regulatory gaps and institutional weaknesses, this paper proposes a hybrid legal framework for carbon trading, anchored in Indonesia’s national ideology, environmental law, and behavioral economic approaches. The article concludes with specific policy recommendations and outlines a roadmap for legislative reform to ensure Indonesia's carbon governance is both globally competitive and locally just.